The diagnostic performance comparison between T2 mapping and Dixon against the activity of thyroid-associated ophthalmopathy: a systematic review and meta-analysis - Zhang, Fuyi; Wang, Pengcheng; Cao, Chun; Pan, Xinyu; Zhang, Tao; Fan, Meng; Guan, Yu (Frontiers in Endocrinology, 2024)
Objective: To compare the diagnostic performance of T2 mapping and Dixon in Thyroid-Associated Ophthalmopathy's disease activity.Methods: Published studies were collected by systematically searching the databases PubMed, Embase, Cochrane Library, Google Scholar, Medline,Web of Science, CNKI, VIP and WANFANG.The sensitivities, specificities, likelihood ratios and diagnostic odds ratio (DOR) were confirmed.The symmetric receiver operator characteristic curve (SROC) was used to assess the threshold of T2 mapping and Dixon. Fagan's nomogram was drawn. Meta-regression and subgroup analyses were applied to distinguish the sources of heterogeneity among the included studies. The review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 statement.Results: A total of 17 studies were included, comprising 1455 participants, including. The combined sensitivity of T2 mapping was 0.70 [95% CI (0.65-0.75)], specificity was 0.84 [95% CI (0.75-0.90)], area under the SROC curve (AUC) was 0.78 [95% CI (0.75-0.82)] and DOR was 12. The combined sensitivity of Dixon was 0.74 [95% CI (0.58-0.85)], specificity was 0.80 [95% CI (0.58-0.93)], AUC was 0.83 [95% CI (0.80-0.86)] and DOR was 11.66. The Deeks' funnel plot showed no existing publication bias. The prospective design, partial verification bias and blinding contributed to the heterogeneity in specificity and sensitivity. The post-test probability of T2 mapping in TAO patients' disease activity was 75%, and the post-test probability of Dixon in TAO was 87%.Compared with T2mapping, Dixon presented the significant higher sensitivity and AUC for detecting TAO disease activity. Dixon is expected to further improve the accuracy of diagnosis of TAO's disease activity.